STRATEGI PENINGKATAN PROFESIONALITAS GURU PENDIDIKAN AGAMA ISLAM DALAM MENYIKAPI PERSAINGAN MUTU PENDIDIKAN DI MTs NIZHAMIYAH PLOSO - Munashofah _; Hidayatur Rohmah (JoEMS (Journal of Education and Management Studies), 2020)
The need for professional teachers is a demand that must be met in order to improve the quality of the education process in schools. This means that teachers have an important role when it comes to education as a place to develop their profession. Therefore, the teacher has a very high responsibility in improving the quality of student development. In this study, researchers used a qualitative method with a naturalistic approach that showed that the research took place naturally, as it was, in normal situations that were not manipulated with the conditions and conditions, emphasizing the description naturally. With this nature, researchers are required to be directly involved in the field by seeing how the professionalism of Islamic Religious Education teachers in improving the quality of education. Based on data findings in the field, that the professionalism of PAI teachers at MTs Nizhamiyah Ploso is depicted in pedagogical abilities; namely the ability of teachers to prepare lesson plans, syllabi, prota and promes, the ability to improvise learning methods and the ability to assess student learning outcomes. personality ability; illustrated by instilling discipline and responsibility in the task. Social ability; illustrated by a good communication relationship with the principal, friends, parents of students and participation in social activities. While the professional ability is described the ability to master the field of study, the ability to understand students, the ability to master learning, the ability to understand the types of subjects, organize subject matter and utilize learning resources.